Emerging Roles of Lipophagy in Health and Disease - Kounakis, Konstantinos; Chaniotakis, Manos; Markaki, Maria; Tavernarakis, Nektarios (Frontiers in Cell and Developmental Biology, 2019)
The term lipophagy is used to describe the autophagic degradation of lipid droplets, the main lipid storage organelles of eukaryotic cells. Ever since its discovery in 2009, lipophagy has emerged as a significant component of lipid metabolism with important implications for organismal health. This review aims to provide a brief summary of our current knowledge on the mechanisms that are responsible for regulating lipophagy and the impact the process has under physiological and pathological conditions.